A study of a flux switching linear generator with a novel speed amplified mechanism and its optimization for the maximum power output and minimum cogging force of wave energy conversion. (1st March 2022) - Liu, Zhenwei; Xiao, Han; Khatri, Pooja; Ding, Songlin; Wang, Xu
Graphical abstract: Highlights: A flux switching electromagnetic wave energy harvester design has been proposed and simulated. The relative speed of the translator has been doubled by a fixed pulley wheel mechanism. The output power was simulated by the ANSYS Maxwell from input design parameters. The peak output power is predicted from the input design parameters using the response surface method. The sensitivity of the design parameters and their interactions has been analysed. The design parameters have been optimized for the maximum peak output power. Abstract: A flux switching electromagnetic wave energy harvester with a novel speed amplified mechanism has been proposed and simulated. The novelty of the design is the relative speed of the translator with respect to the stator being doubled through a fixed pulley wheel mechanism. The output power was simulated by the ANSYS Maxwell module from input design parameters. The relationship between the input design parameters and target peak power output has been established through the simulation to understand the science. The sensitivity of the design parameters and their interactions has been studied through the Taguchi method (Design of Experiment) and response surface methodology (RSM). The design parameters of the stator and arrangement of the magnet configuration have been optimized for the maximum peak output power. The RSM model has been validated by the analysis of the variance method. The optimal results of the RSM model have been verified by the ANSYS simulation results. The RSM is proven to be a useful tool for design and optimization of the linear generator take-off unit. The cogging force has also been minimized by optimizing the dimensions of the feet on the stators using the RSM. The analysis and simulation methods have contributed to new knowledge of the flux switching electromagnetic wave energy harvester.